Answers

2016-01-30T16:53:06+05:30
(sinA + secA)² + (cosA + cscA)² 

= (sinA + 1/cosA)² + (cosA + 1/sinA)² 

= sin²A + 2sinA/cosA + 1/cos²A + cos²A + 2cosA/sinA + 1/sin²A 

= (sin²A + cos²A) + (2sinA/cosA + 2cosA/sinA) + (1/cos²A + 1/sin²A) 

= 1 + 2(sin²A+cos²A)/(sinAcosA) + (sin²A+cos²A)/(sin²Acos²A) 

= 1 + 2/(sinAcosA) + 1/(sin²Acos²A) 

= (1 + 1/(sinAcosA))² 

= (1 + secA cscA)²  

= (1 + 1/(sinAcosA))² 

= (1 + (sin²A+cos²A)/(sinAcosA))² 
= (1 + sin²A/(sinAcosA) + cos²A/(sinAcosA))² 
= (1 + sinA/cosA + cosA/sinA)² 

= (1 + tanA + cosA)² 
0